2013
DOI: 10.5489/cuaj.269
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of combined medication of two different antimuscarinics for treatment of adults with idiopathic overactive bladder in whom a single agent antimuscarinic therapy failed

Abstract: Objective: Recent studies have investigated a combination of two antimuscarinics for adult neurogenic bladder managed with clean intermittent catheterization or pediatric refractory overactive bladder (OAB). We assessed the efficacy and tolerability of this strategy in adults with idiopathic OAB. Methods: We reviewed 49 patients with idiopathic OAB who received combined antimuscarinic medication. Patients had serially received different kinds of antimuscarinics as monotherapy, but wished to take combined medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
(28 reference statements)
1
13
0
Order By: Relevance
“…The three studies, which had cohorts of 177 to 313 individuals, demonstrate that compared to placebo, combinations of trospium and solifenacin result in decreases in urinary urgency and urge incontinence, though only one of the studies achieves statistical significance. Likewise, Yi et al found that in 49 patients, the combination therapy of propiverine or tolteridine with another anticholinergic medication improves urinary urgency and urge incontinence compared to baseline monotherapy in a statistically significant manner.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The three studies, which had cohorts of 177 to 313 individuals, demonstrate that compared to placebo, combinations of trospium and solifenacin result in decreases in urinary urgency and urge incontinence, though only one of the studies achieves statistical significance. Likewise, Yi et al found that in 49 patients, the combination therapy of propiverine or tolteridine with another anticholinergic medication improves urinary urgency and urge incontinence compared to baseline monotherapy in a statistically significant manner.…”
Section: Resultsmentioning
confidence: 99%
“…Four articles were identified that examined the use of anticholinergic medications in combination with each other (Table ) . Three of the four studies were conducted by Kosilov et al at the Institute of Physical Health in Russia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amend and colleagues also hypothesized that patients refractory to highdosage monotherapy might be fast metabolizers who would benefit from higher doses. 21 Finally, as suggested by other groups, 21,22 there could be a synergistic or additive effect of both drugs on the receptors. Considering that the pathophysiology of overactive bladder is not fully understood, there is clearly a need for more research to shed light on the exact mechanism of action.…”
mentioning
confidence: 78%
“…Limited evidence has revealed that combined high‐dosed therapy is effective and safe for treating refractory neurogenic detrusor overactivity . Recently, Yi et al showed the efficacy and tolerability of two different antimuscarinics in adults with idiopathic OAB refractory to a single antimuscarinic agent . However, this retrospective study used at least 10 heterogeneous combined antimuscarinics.…”
Section: Introductionmentioning
confidence: 99%